Dye Sorption from Textile Wastewater onto Faujasite Zeolite Synthesized from Bauxite Sediment and Rice Husk Silica (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This study explores the adsorptive properties of high silica-containing zeolite synthesised from natural sediments rich in aluminosilicates, modified with biowaste silica for wastewater treatment. Hydrothermal synthesis was used to produce zeolite from local clay sediment. The synthesised zeolite was tested for its ability to adsorb ionic dyes from textile wastewater. XRD and EDS analysis revealed a faujasite zeolite-Y with 85.60 g of Si and 17.50 g of Al, and a Si/Al ratio of 4.891 g/mol. The Zeolite Y particles had a uniform size distribution ranging from 1 to 3 μm. The Langmuir isotherm analysis showed a specific surface area of 1,750 m²/g and a pore diameter of 1.847 nm. Batch adsorption experiments yielded Langmuir, Freundlich, and Temkin regression constants with R² values below 0.9924, 0.9451, and 0.9395, respectively, during an isothermal study on methylene blue sorption. The fixed-bed column test indicated an adsorbent stability of 5.25 hours. Overall, the faujasite zeolite-Y, with its large mesoporous structure, demonstrates significant adsorption of ionic dye from textile effluent.